2019
DOI: 10.1021/acs.oprd.9b00210
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Benzylic Alkylation of Benzylic Carbonates: Improvement of Palladium Catalyst and Mechanistic Study

Abstract: The palladium catalyst for the nucleophilic substitution of benzyl carbonates was improved by using 1,1′-bis­(diisopropylphosphino)­ferrocene (DiPrPF) as the ligand. The [Pd­(η3-C3H5)­(cod)]­BF4–DiPrPF catalyst allows the benzylic substitution with soft carbanions to proceed even at 30 °C, affording the desired products in high yields (up to 99% yield). Thermally unstable pyridylmethyl esters are employable as the electrophilic substrates for the benzylic alkylation with the improved catalyst. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Therefore, while we can unambiguously exclude antarafacial shifts, we cannot provide spectroscopic evidence for the presence or absence of a suprafacial process. However, on the basis of precedent in closely related compounds and on relative energetics from DFT studies ( vide infra ), we conclude that suprafacial shifts are indeed rapid on the NMR time scale in 1 – 14 , and the observed spectra are the result of this averaging process.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, while we can unambiguously exclude antarafacial shifts, we cannot provide spectroscopic evidence for the presence or absence of a suprafacial process. However, on the basis of precedent in closely related compounds and on relative energetics from DFT studies ( vide infra ), we conclude that suprafacial shifts are indeed rapid on the NMR time scale in 1 – 14 , and the observed spectra are the result of this averaging process.…”
Section: Resultsmentioning
confidence: 74%
“…The NMR spectra of numerous [ML 2 (η 3 -benzyl)] n + complexes were consistent with fast suprafacial shifts on the NMR time scale at room temperature. As a prelude to further discussion of related chiral complexes, Schemes – provide more background on NMR studies of dynamic processes in these compounds, for which the number of possible isomers depends on the symmetry of the ligands (Scheme ). Their observed speciation depends on the relative isomer energies and on the rates of the suprafacial and antarafacial shifts on the NMR time scale.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[ 25 ] The nucleophilic substitution reaction of the halo‐organic compounds with carboxylic acids is one of the most well‐known reactions practiced to modernize. [ 26,27 ] The reaction between aromatic and simple aliphatic alcohols could be carried out to prepare esters utilizing different photocatalysts in aqueous media through C‐H activation. [ 28 ] Lipase‐catalyzed ester synthesis is another approach discussed in the literature that explains the effect of different media, alcohol, and acyl donors.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate I would isomerize into the η 3 -benzylnickel intermediate II , and the intermediates I and II might be in equilibrium. , Finally, the reaction of the cationic η 3 -benzylnickel intermediate II with a malonate anion seems to take place to produce the desired alkylation product 8 or 9 . Although the reactivity difference between the benzylnickel species I and II with a malonate anion is unclear at this stage, we believe that the malonate anion would attack the cationic η 3 -benzylnickel II based on the detailed mechanistic study of the palladium-catalyzed benzylic alkylation reaction recently reported by Kuwano and co-workers …”
mentioning
confidence: 99%